2021
DOI: 10.1186/s12877-021-02078-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of an acceptance and commitment therapy intervention for caregivers of adults with Alzheimer’s disease and related dementias

Abstract: Background Caregivers of patients with Alzheimer’s disease or a related dementia (ADRD) report high levels of distress, including symptoms of anxiety and depression, caregiving burden, and existential suffering; however, those with support and healthy coping strategies have less stress and burden. Acceptance and Commitment Therapy (ACT) aims to foster greater acceptance of internal events while promoting actions aligned with personal values to increase psychological flexibility in the face of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…These studies showed how ACT was effective in reducing depressive (15, 43-47), and anxiety symptoms (15, 42,44,47). Regarding anxiety, the results are less consistent, with studies concluding that ACT could reduce anxiety symptoms (15, 42,44,47) and other studies finding that it does not (43,45,46).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These studies showed how ACT was effective in reducing depressive (15, 43-47), and anxiety symptoms (15, 42,44,47). Regarding anxiety, the results are less consistent, with studies concluding that ACT could reduce anxiety symptoms (15, 42,44,47) and other studies finding that it does not (43,45,46).…”
Section: Discussionmentioning
confidence: 96%
“…These studies showed how ACT was effective in reducing depressive (15, 43-47), and anxiety symptoms (15, 42,44,47). Regarding anxiety, the results are less consistent, with studies concluding that ACT could reduce anxiety symptoms (15, 42,44,47) and other studies finding that it does not (43,45,46). One of the studies (47) compared the benefits of ACT with those of traditional CBT, concluding that both procedures effectively reduce symptoms of anxiety and depression.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The empirical findings have been valuable in describing how values and committed action core processes provide potential benefits for staff working in nursing home settings; however, no study has examined the effects of both processes (which results in engaged living) conducted in group intervention setting among nursing home staff. Several studies found positive effects of ACT for family caregivers of adults with dementia (Fowler et al, 2021;Losada et al, 2015). ACT conducted in group setting also provides new findings when conducted among caregivers of chronic illness patients (Williams et al, 2014) and among informal caregivers of people with psychosis (Jolley et al, 2020).…”
Section: Introductionmentioning
confidence: 95%